Gender budgeting: A contextual analysis of the higher-education sector in Albania - Brunilda Llaftiu; Ingrid Shuli (Administrative Sciences, 2024)
In this study, we chose to conduct a gender-based contextual analysis of research-performing organizations (RPOs) in the higher-education sector in Albania as a first step toward the implementation of gender budgeting (GB). Our rationale for conducting such a contextual analysis is the overarching need to achieve the European Commission's strategic objectives regarding gender equality in research and innovation. To carry out this analysis, we used reports from She Figures to calculate dominant gender indicators; these reports were produced in collaboration with the statistics published by the Institute of Statistics of Albania. Our methodology is based on a mixed-methods approach that aims to better our understanding of the situation in Albania. The quantitative findings provided by our contextual analysis within academia were synthesized with qualitative findings resulting from a comparative analysis of the content of gender equality plans (GEPs) currently being implemented by thirteen universities in Albania. The results of our contextual analysis study show that even though women account for more than half of the total population of researchers at the national level, playing a significant role in research and innovation, we recommend that the government develop its first national GEP to counteract the inequality that persists in the career trajectories of women and men. GB represents an effective strategy for reducing gender inequality in this context. The supporting results of the content analysis indicate that the phenomenon of vertical segregation has been identified in the great majority of RPOs that have carried out gender-based contextual analyses; moreover, we observed the interaction of GB with GEPs within three such organizations' approach to the gender-based allocation of finances.
Keywords: 350; gender budgeting; gender contextual analysis; gender equality plan; gender-sensitive indicators; research-performing organizations (RPOs)